Front Cover: Eleven New Triterpenoid Glycosides from the Roots of Ilex asprella (C&B 7/2019). Issue 7 (25th June 2019) - Huang, Xiao‐Jun; Wen, Si; Guan, Xi‐Feng; Wu, Zhen‐Long; Li, Man‐Mei; Fan, Chun‐Lin; Zhang, Qing‐Wen; Chan, Ging; Wang, Ying; Ye, Wen‐Cai
Abstract : Front Cover . The plant Ilex asprella (Aquifoliaceae) is a shrub mainly distributed in southern area of China. The roots of I. asprella, named 'Gang‐Mei‐Gen' in Chinese, are commonly used as a folk medicine and one of the major ingredients of several popularly consumed herbal teas in Lingnan region. In our continuing investigation on bioactivity constituents of medicinal herbs in the region of Lingnan, eleven new triterpenoid glycosides, named as Asprellosides A−K, including six rare sulfated triterpenoid glycosides were isolated from the roots of I. asprella . Two new compounds represent the first examples of triterpenoid glycosides bearing a rare 3, 4‐ O ‐disulfo‐xylopyranosyl residue as reportet by X.‐J. Huang et al, in their full paper at10.1002/cbdv.201900202 .